Relationship between plasma sex steroids and cell proliferation-related gene expression in the uterus during dioestrus in nonpregnant bitches. - Gossler, Vanessa da Silva Alves; Nunes, Sarah Gomes [UNESP]; Garcia Santos, Francislaine Anelize; de Oliveira Santos, Aline; Mattoso Miskulin Cardoso, Ana Paula; Papa, Paula de Carvalho; Marçal, Natalia Caroline de Oliveira; de Souza, Lilian Francisco Arantes; Castilho, Caliê; Floriano, Rafael Stuani; Giometti, Ines Cristina (CSIRO Publishing, 2025)
CONTEXT: Reproductive processes in mammals involve complex interactions between sex steroids and growth factor systems. Understanding these interactions in the uterus during different stages of the reproductive cycle is essential for elucidating the mechanisms of endometrial regulation. AIMS: This study aimed to investigate the relationship between circulating sex steroids and the expression of genes involved in the insulin-like growth factor 1 (IGF1) system and steroid hormone receptors in the uterine horns of non-pregnant bitches during dioestrus. METHODS: Uterine horns from 29 bitches were collected surgically at 10, 20, 30, 40, 50, and 60 days post-ovulation (n = 4 or 5 per group). Relative mRNA abundances of IGF1 system genes (IGF1, IGFR1, IGFBP3, IGFBP4, PAPPA) and steroid hormone receptors (PGR, ESR1, ESR2) were determined by RT-qPCR. Blood samples collected at surgery were analysed for oestradiol and progesterone concentrations. Correlations between hormone levels and gene expression were assessed. KEY RESULTS: ESR2 gene expression declined at 40 and 50 days post-ovulation compared to 30 days or earlier, and was positively correlated with progesterone and negatively with the oestradiol/progesterone ratio. IGFBP3 expression increased progressively through dioestrus, while IGFBP4 expression rose at the later stages (50 and 60 days), showing a negative correlation with progesterone and a positive correlation with the oestradiol/progesterone ratio. CONCLUSIONS: Reduced ESR2 gene expression at 40 days of dioestrus may reflect a uterine environment permissive to local cell proliferation, suggesting dynamic hormonal modulation of endometrial responsiveness. IMPLICATIONS: The gradual increase in IGFBP3 and IGFBP4 gene expression throughout dioestrus indicates a potential role for these binding proteins as modulators of IGF1 bioavailability, contributing to the fine-tuning of uterine tissue remodelling in non-pregnant bitches.